The Effect of Cold Temperature on the Severity of Allergic Rhinitis Based on Visual Analog Scale (VAS) Score Among Medical Students of Malikussaleh University - Farianti Zuhra; Mulyati Sri Rahayu; Baluqia Iskandar Putri (RSUP Dr. Kariadi, 2024)
BACKGROUND: Allergic rhinitis is a common condition caused by inflammation of the nasal mucosa after exposure to allergens and is mediated by Immunoglobulin E (IgE). Cold temperatures can aggravate the symptoms of allergic rhinitis. Allergic rhinitis is not fatal, but it can cause a decrease in the patient's quality of life if the symptoms are severe. The severity of allergic rhinitis symptoms is difficult to measure as it should match patient's perception, so VAS is a quantitative measurement tool used. Although VAS is a simple and easy-to-use tool, its use as self-monitoring for AR patients is still infrequent to minimize symptom exacerbations and maintain control of allergic rhinitis. AIMS: This study aims to examine the effect of cold temperature on the severity of allergic rhinitis based on VAS score. METHOD: This research is an experimental with a one-group pretest-posttest study. The study samples involved 75 students suffering from allergic rhinitis assessed with the Score for Allergic Rhinitis (SFAR) questionnaire assessment from the class of 2020, 2021, and 2022. Subjects’ pain level was measured before and after the intervention. The intervention was in the form of cold temperature exposure for 15 minutes in a room with a temperature of 18℃. Data were analyzed using the Wilcoxon test. RESULT: The results showed that the mean VAS score before the intervention was 0 while after the intervention was 38.61 ± 24.07. This shows that the mean VAS score after the intervention is higher than the mean VAS score before the intervention (p-value = 0.00 <0.05). CONCLUSION: The results of this study indicate that the effect of cold temperature can increase the severity of allergic rhinitis.